Maternal Obesity/Diabetes, Plasma Branched‐Chain Amino Acids, and Autism Spectrum Disorder Risk in Urban Low‐Income Children: Evidence of Sex Difference. Issue 10 (9th August 2019) - Panjwani, Anita A.; Ji, Yuelong; Fahey, Jed W.; Palmer, Amanda; Wang, Guoying; Hong, Xiumei; Zuckerman, Barry; Wang, Xiaobin
Abstract : Maternal metabolic conditions are known risk factors for child autism spectrum disorder (ASD). Branched‐chain amino acids (BCAAs) are also associated with ASD. We examined the joint associations of maternal metabolic conditions and BCAAs on the risk of child ASD and whether the associations differed by child's sex. We analyzed 789 mother–infant pairs, a subset of the Boston Birth Cohort, from a predominantly urban, low‐income, minority population. Maternal plasma BCAAs were measured by liquid chromatography–tandem mass spectrometry in samples collected 24–72 hr postpartum. A composite BCAA score was created using factor analysis, and prepregnancy obesity and diabetes (ob/DM) were combined into one variable. Logistic regression was used to explore the role of BCAAs as mediators or cofactors with ob/DM and child's sex on ASD risk. BCAA‐ob/DM and BCAA‐sex interactions were also examined. Maternal BCAAs alone were not associated with ASD and did not mediate the path between ob/DM and ASD. In the presence of maternal ob/DM, BCAA score was significantly associated with ASD (adjusted OR 2.33, 95% CI 1.18, 4.60). Interactions were present for valine with ob/DM and for valine and isoleucine with male sex on ASD risk. The odds ratio (OR) for risk of ASD was the greatest with all three risk factors combined—male sex, above median BCAA score, and ob/DM (OR 10.79, 95% CI 4.40, 26.42). Similar patterns were found for other developmental disorders, though not as strong as for ASD. Additional studies are warranted to clarify the role of maternal BCAAs, ob/DM, and child's sex in ASD. Autism Res 2019, 12: 1562–1573 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: This study investigated whether maternal obesity/diabetes and maternal circulating branched‐chain amino acids (BCAAs) can jointly affect child ASD risk and whether the associations differ by child's sex. We found that the risk of ASD was greater among mothers with obesity/diabetes who also had elevated concentrations of BCAAs and that this risk was even greater for male children. These findings provide new evidence on fetal origins of ASD and sex difference and warrant additional investigation.